2000
DOI: 10.1093/ajcn/71.6.1392
|View full text |Cite
|
Sign up to set email alerts
|

Measures of body composition in blacks and whites: a comparative review

Abstract: Biological differences exist in the body composition of blacks and whites. We reviewed literature on the differences and similarities between the 2 races relative to fat-free body mass (water, mineral, and protein), fat patterning, and body dimensions and proportions. In general, blacks have a greater bone mineral density and body protein content than do whites, resulting in a greater fat-free body density. Additionally, there are racial differences in the distribution of subcutaneous fat and the length of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
264
4
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(291 citation statements)
references
References 48 publications
11
264
4
5
Order By: Relevance
“…Race, which reflects both the inheritance of genetic characteristics and can represent a proxy for socioeconomic conditions, is also associated with obesity 3,23,28,60 . The populations evaluated in the current review consisted of quite homogeneous ethnic groups, so they did not allow evaluating this variable's impact on abdominal obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Race, which reflects both the inheritance of genetic characteristics and can represent a proxy for socioeconomic conditions, is also associated with obesity 3,23,28,60 . The populations evaluated in the current review consisted of quite homogeneous ethnic groups, so they did not allow evaluating this variable's impact on abdominal obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Our study, although with a smaller sample size, confirmed the highest proportion of obesity in women and a complete absence of overweight and obesity in YM, which appeared to be clearly related to their regular physical activity. The appropriateness of some direct (hydrodensitometry) and indirect (skinfolds, BIA) body composition methods has been questioned for some non-western populations (Deurenberg and Yap, 1999;Wagner and Heyward, 2000). A recent review by Wagner and Heyward (2000) suggested that, because of the higher bone mineral content (BMC) of blacks, the most accurate technique for body composition measurement is the dual energy X-ray absorptiometry (DEXA), since it measures and divides lean body mass (LBM) from BMC, while the hydrodensitometric method, which lacks this property, could produce an overestimation of FFM.…”
Section: Urbanization and Obesity In The Gambiamentioning
confidence: 99%
“…There is increasing evidence that the assumption of a constant density of the LBM is not valid across populations groups, for example blacks have a higher density of LBM than whites (Ortiz et al, 1992;Wagner & Heyward, 2000, 2001. Specific formulas have been recommended for converting body density to %BF in black men (Wagner & Heyward, 2000) and women (Ortiz et al, 1992).…”
Section: Air Displacement Plethysmographymentioning
confidence: 99%
“…Specific formulas have been recommended for converting body density to %BF in black men (Wagner & Heyward, 2000) and women (Ortiz et al, 1992). For this reason, %BF ADP was calculated from body density taking into account the value of 1.106 kg/l given by Ortiz et al (1992) for the density of LBM in black women, and the value of 0.9007 kg/l for the density of fat used in black men by Wagner and Heyward (2001).…”
Section: Air Displacement Plethysmographymentioning
confidence: 99%